2005
DOI: 10.1890/03-5374
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Species Distribution Predictions: A Simulation Modeling Experiment

Abstract: Geospatial species sample data (e.g., records with location information from natural history museums or annual surveys) are rarely collected optimally, yet are increasingly used for decisions concerning our biological heritage. Using computer simulations, we examined factors that could affect the performance of autologistic regression (ALR) models that predict species occurrence based on environmental variables and spatially correlated presence/absence data. We used a factorial experiment design to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 30 publications
3
105
0
3
Order By: Relevance
“…False absences result from insufficient sampling effort given the species' abundance or detectability. They can hinder good model performance, although Reese et al (2005) showed that randomly distributed false absences, due to randomly biased sampling effort, do not. True absences can be further subdivided into two classes: "true environmental" absences, when the species is not present due to environmental constraints on its physiology; and contingent absences, when the environment is appropriate but other factors such as limitations to dispersal, elimination by anthropogenic or stochastic events, or biotic interactions prevent species occurrence .…”
Section: Introductionmentioning
confidence: 99%
“…False absences result from insufficient sampling effort given the species' abundance or detectability. They can hinder good model performance, although Reese et al (2005) showed that randomly distributed false absences, due to randomly biased sampling effort, do not. True absences can be further subdivided into two classes: "true environmental" absences, when the species is not present due to environmental constraints on its physiology; and contingent absences, when the environment is appropriate but other factors such as limitations to dispersal, elimination by anthropogenic or stochastic events, or biotic interactions prevent species occurrence .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, sampling biases can confound the development of tenable species distribution models. Although algorithms for predicting species distributions that are robust to such sampling biases are being investigated (Peterson 2001;Hirzel and others 2002;Reese 2003), use of this database to construct inferential models must explicitly consider effects associated with potentially biased sampling effort.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling error can also occur when observers differ in their ability to detect, identify and quantify species or events [32], leading to variation in data accuracy [10,34,35]. Sample size, coupled with species' ecological and detection differences can alter the performance of distribution models [36]. Consequently, inadequate evaluation of these biases associated with citizen science data will lead to false results that fail to accurately describe the species distribution.…”
Section: Introductionmentioning
confidence: 99%